Aptamer-functionalized stiff hydrogel for enhanced BMSC enrichment and osteogenesis - Jifeng Jing; Fengyu Li; Yu Wang; Shuo Cheng; Lei Guo (PLoS ONE, 2026)
To address the need to both enrich stem cells and direct their osteogenic fate in bone tissue engineering and bone regeneration, we developed a stiffness-gradient hydrogel (~4.5– 33 kPa) functionalized with a cell-enriching aptamer (Apt19s). This design forms a combined “enrich-and-differentiate” system: Apt19s actively enriches endogenous bone marrow-derived mesenchymal stem cells (BMSCs) at the scaffold site, while the osteoinductive high-stiffness niche (~ 33 kPa) directs their differentiation. Crucially, the combined cues produced an enhanced osteogenic outcome—evidenced by significantly greater alkaline phosphatase (ALP) activity (>2-fold increase), upregulated RUNX2/osteocalcin (OCN) gene expression (186.5% relative to control), and enhanced mineralization—that surpassed the additive effects of either cue presented independently. This integrated platform provides a practical strategy for developing cell-free osteogenic materials that actively tackle the dual challenges of endogenous cell sourcing and lineage-specific induction.